Software metrics : a rigorous and practical approach - Fenton, Norman E., 1956-; Bieman, James (Boca Raton : CRC Press, Taylor & Francie Group, 2014)
'This book provides an up-to-date and rigorous framework for controlling, managing, and predicting software development processes. Emphasizing real-world applications, the authors apply basic ideas in measurement theory to quantify software development resources, processes, and products. The text offers an accessible and comprehensive introduction to software metrics. It features extensive case studies in addition to worked examples and exercises. This new edition covers current research and practical applications of cost estimation methods in practice'--
Part 1. Fundamentals of measurement and experimentation -- part 2. Software engineering measurement.
Includes bibliographical references : pages 555-576 and index.
Keywords: Software measurement; Computer software -- Evaluation